Analisis Faktor Kepatuhan Berobat Berdasarkan Skor MMAS-8 pada Pasien Diabetes Mellitus Tipe 2 - Siti Julaiha (Politeknik Kesehatan Tanjung Karang, 2019)
Diabetes mellitus is a chronic metabolic disease known as a deadly killer. Indonesia ranks 5th in the world in the number of people with Diabetes Mellitus in 2014. Poor medication adherence can increase microvascular and microvascular complications that cause damage to organs such as fat, heart, brain, and eyes. Patient adherence can be measured using a questionnaire 8- Morisky item Medication adherence Scale (MMAS-8). This instrument can be used to measure medication adherence in patients with chronic diseases such as hypertension, diabetes mellitus, tuberculosis, etc. This study aimed to analyze the factors associated with Medication Adherence Based On MMAS-8 Score to Type 2 Diabetes Mellitus Outpatient at Mardi Waluyo Hospital Metro in 2018. This research is an analytic observational study with a design cross-sectional study. The population of this study was type 2 DM outpatients who were treated at Mardi Waluyo Hospital Metro in 2018. The data collected were the results of research using the MMAS-8 questionnaire. Data were analyzed by using chi-square and multivariate logistic regression method. Result of this study showed that the patient who has income <Rp 2,100,000 risk nonadherence 2,981 times higher than a patient who has an income of ≥Rp.2,100,000. Patients with primary education risk nonadherence 2.724 times higher than patients with further education.